High rate of hematological responses to sorafenib in FLT3‐ITD acute myeloid leukemia relapsed after allogeneic hematopoietic stem cell transplantation. (21st September 2015) - De Freitas, Tiago; Marktel, Sarah; Piemontese, Simona; Carrabba, Matteo G.; Tresoldi, Cristina; Messina, Carlo; Lupo Stanghellini, Maria Teresa; Assanelli, Andrea; Corti, Consuelo; Bernardi, Massimo; Peccatori, Jacopo; Vago, Luca; et al.
Abstract: Relapse represents the most significant cause of failure of allogeneic hematopoietic stem cell transplantation (HSCT) for FLT3‐ITD‐positive acute myeloid leukemia (AML), and available therapies are largely unsatisfactory. In this study, we retrospectively collected data on the off‐label use of the tyrosine kinase inhibitor sorafenib, either alone or in association with hypomethylating agents and adoptive immunotherapy, in 13 patients with post‐transplantation FLT3‐ITD‐positive AML relapses. Hematological response was documented in 12 of 13 patients (92%), and five of 13 (38%) achieved complete bone marrow remission. Treatment was overall manageable in the outpatient setting, although all patients experienced significant adverse events, especially severe cytopenias (requiring a donor stem cell boost in five patients) and typical hand‐foot syndrome. None of the patients developed graft‐vs.‐host disease following sorafenib alone, whereas this was frequently observed when this was given in association with donor T‐cell infusions. Six patients are alive and in remission at the last follow‐up, and four could be bridged to a second allogeneic HSCT, configuring a 65 ± 14% overall survival at 100 d from relapse. Taken together, our data suggest that sorafenib might represent a valid treatment option for patients with FLT3‐ITD‐positive post‐transplantation relapses, manageable also in combination with other therapeutic strategies.